MODELING BILL-OF-MATERIAL WITH TREE DATA STRUCTURE: CASE STUDY IN FURNITURE MANUFACTURER - Prahasto, Toni (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2008)
This paper presents a modeling of Bill-of-Material with tree data structure. The BOM represents wooden furniture products. The management of BOM is incorporated into an MRP software which is specially built for a furniture manufacturer. The tree data structure is approached with an object oriented programming to provide the creation and modification of the data. The tree object is designed so that a downstream programmer can create an application with high productivity, using the BOM object of course. Legality of the development is ensured by adapting open source resources, i.e. MySQL database engine, PHP server script, and client-side Javascript. The BOM object is used extensively in the MRP software that is being developed. A couple of screenshots are presented to demonstrate the ease of creation and manipulation of Bill-of-Material. The proper approach of modeling BOM with tree structure allows the programmer to reach high productivity during the development of the aforementioned MRP customized software. Keyword : Modeling, Bill of Material, Tree Data Structure